Research of Power System Closest Voltage Collapse Boundary - Yi, Tao; Wang, Cheng-Min; Sun, Wei-Qing; Zhang, Yan (Elektronika ir Elektrotechnika, 2013)
The determination of power system voltage collapse boundary is very important to study voltage stability. The explicit expressions of power system voltage high and low voltage curves are obtained by solving the equations which are formed by the hybrid network equations and then get the characteristic equations of the voltage collapse boundary. For analyzing the closest boundary by the characteristic equations we define the one-node voltage collapse boundary and all-node voltage collapse boundary. The closest stability boundary of the power system has been found out by comparing the active power index. Because the Jacobian matrix is singular near the voltage collapse boundary the dimensionality reduced algorithm is proposed. This method can get the value of voltage collapse boundary effectively. The simulations show that the concepts and methods presented in this paper are correct. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5890